2012
DOI: 10.4067/s0718-58392012000400020
|View full text |Cite
|
Sign up to set email alerts
|

Insecticied effect of silver and zinc nanoparticles against Aphis nerii Boyer of fonscolombe (Hemiptera: Aphididae)

Abstract: The oleander aphid, Aphis nerii Boyer de Fonscolombe, is one of the common pests of ornamental plants in the families of Apocynaceae and Sclepiadaceae and distributed throughout the world, which has been responsible for the mortality of a large number of oleander (Nerium oleander L.) shrubs each year. In this research, the insecticidal activity of Ag nanoparticles against the A. nerii was investigated. Nanoparticles of Ag and Ag-Zn were synthesized through a solvothermal method, and using them, insecticidal so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 16 publications
4
28
0
Order By: Relevance
“…Rouhani et al. () found that AgNPs were toxic to the oleander aphid, Aphis nerii , a pest of some ornamental plants. They compared the LC 50 values of the nanoparticles and a neonicotinoid insecticide, imidacloprid, finding the aphids were far more susceptible to the insecticide than the AgNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Rouhani et al. () found that AgNPs were toxic to the oleander aphid, Aphis nerii , a pest of some ornamental plants. They compared the LC 50 values of the nanoparticles and a neonicotinoid insecticide, imidacloprid, finding the aphids were far more susceptible to the insecticide than the AgNPs.…”
Section: Discussionmentioning
confidence: 99%
“…In the comparison made between acaricidal, licicidal and larvicidal activities of zinc oxides and the synthesized ZnO nanoparticles, the mortality effect of ZnO nanoparticles was significant (Kirthi et al, 2011). Rouhani et al (2012) (Burckhardt and Lauterer, 1989)) and found out a greater insecticidal effect of Amitraz than the above nanoparticles. It should be taken into consideration that nanoparticles, especially the synthesized zinc nanopartilces, besides their insecticidal activity and also their slower effect than imidacloprid and Amitraz insecticides, have a lower risk of resistance to these nanoparticles in comparison to commercial insecticides .…”
Section: Figure 4: Ftir Of Synthesized Zno Nanoparticlesmentioning
confidence: 99%
“…Application of nanomaterials can revolutionize agriculture by developing potential and effective methods for pest management (Rai and Ingle, 2012). Some studies have reported the toxic effects of metal nanoparticles (such as silver, zinc, aluminum, and titanium oxide) on plants, crustaceans, bacteria, fungi, pathogens and pests (Elchiguerra et al, 2005;Goswami et al, 2010;Kairyte et al, 2013;Kirthi et al, 2011;Manzo et al, 2011;Morones et al, 2005;Reddy et al, 2007;Rouhani et al, 2012;Samuel and Guggenbichler 2004). Among them, zinc oxide (ZnO) nanoparticle is best-known compound (Mitra et al, 2012) commonly used as agricultural fungicide (Waxman 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The LC 50 , respectively, were found to be a valuable tool in pest management programs of the oleander aphid, Aphis nerii Boyer de Fonscolombe, one of the common pests of ornamental plants, which is responsible for the mortality of a large number of oleander (Nerium oleander) shrubs each year [206].…”
Section: Nanoinsecticidesmentioning
confidence: 99%